Shikhara (superstructure) of the Adinatha Temple - Temples of India Project Team (Jio Institute, 2024)
The Shikhara (superstructure) of the Adinatha Temple is built in the Nagara style, albeit an abbreviated one. The mulshringa of the shikhara has a pratyangas or prati shikharas emanating from it. These are complemented by miniature shikharas at the base of the main shikhara. The shikhara is painted in white and the ornamentation details are defined with gold paint. The base of the cardinal faces of the shikhara has deep empty niches, similar to the shikhara of the Bhandasar Temple.